PEMBERIAN MP-ASI DAN STATUS GIZI BALITA YANG BERKUNJUNG KE PUSKESMAS ANGGUT ATAS KOTA BENGKULU - Nurul Khairani; S Effendi; Yuniarti Yuniarti (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Impact of malnutrition in children under five can lead to failure of physical growth and development of intelligence, increase morbidity and mortality, especially in infants, reduce productivity and lower endurance. This study aimed to study the association between complementary feeding practice with nutritional status in children under five who visited Anggut Atas Public Health Center Bengkulu. The type of research used was Analytical Survey with Cross Sectional design. The population in this study was all mothers who had children aged 6-24 months who visited Anggut Atas Public Health Center Bengkulu. Sample technique was Accidental Sampling which amounted to 52 mothers. The data used were primary and secondary data. Data analysis technique used was univariate and bivariate analysis with Chi-Square statistical test and to know the closeness of relationship used Contigency Coefficient (C) test. The results of this study found that of 52 mothers, there were 33 mothers (63.5%) who gave early breast-feeding, 37 mothers (71.2%) who had children under five with good nutritional status, and there was a significant association between complementary feeding practice with nutritional status in children under five who visited Anggut Atas Public Health Center Bengkulu with medium relations category. Suggestions for Anggut Atas Public Health Center Bengkulu can provide education about complementary feeding practice to mothers of children under five in the working area of Anggut Atas Public Health Center Bengkulu. Keywords : children under five, complementary feeding practice, nutrition status